Penggunaan Material Komposit Sebagai Komponen Pintu Air Alternatif - Aditya Prihantoko; Marasi Deon Joubert; Dadan Rahmandani (Balai Teknik Irigasi, 2015)
Irrigation network operation is an important part of the irrigation management system. Operating on an irrigation area (DI) requires the performance of human resources (jurupengairan) and divider building infrastructure, in this case irrigation water gate, in a good performance. Water gate material is mostly made up of steel or wood which is susceptible to damage and theft .As alternative material of sluice, can be considered the use of composite material which has an advantage can save cost and makes the lighter material is used as an opportunity for alternative irrigation water gate. So it is necessary to research on material other than stell or wood. The methodology that used in this study was test several alternative types of composite material to be used as irrigation water gate in the laboratory and then conduct an analysis of water gate loading. Results of laboratory testing and analysis of the load for a water gate with 50 cm width and maximum height of water about 60 cm showed that type 1, 2 and 3 are able to withstand the load of more than 1000%, 440 % and 320 %, respectively of the load. These results indicate that a composite is strong enough if used as an alternative material for water gate.